Sacred thresholds: the door to the sanctuary in late antiquity - Opstall, Emilie Marlène van (Religions in the Graeco-Roman world, 2018)
Front Matter -- Copyright page -- List of Figures -- List of Contributors -- General Introduction -- Experiencing Sacred Thresholds -- On the Threshold -- Entering the Baptistery /Juliette Day -- From Taboo to Icon /Christian Boudignon -- Bonus Intra, Melior Exi! /Ildikó Csepregi -- Symbolism and Allegory 0f Sanctuary Doors -- Sanctuary Doors, Vestibules and Adyta in the Works of Neoplatonic Philosophers /Lucia M. Tissi -- The Paradise of Saint Peter’s /Sible L. de Blaauw -- Imagining the Entrance to the Afterlife /Roald Dijkstra -- Messages in Stone -- The Queen of Inscriptions Contextualized /Evelien J.J. Roels -- Versus De Limine and In Limine /Gianfranco Agosti -- The Door to the Sanctuary from Paulinus of Nola to Gregory of Tours /Gaëlle Herbert de la Portbarré-Viard -- The Presence of the Divine -- Filters of Light /Christina G. Williamson -- The Other Door to the Sanctuary /Brooke Shilling -- Back Matter -- General Index.